Modules for the Technical Skills Section of the OSCE Component of the American Board of Anesthesiology APPLIED Examination - Lauryn R. Rochlen; Vijay Tarnal; Jennifer L. Vance; Erik Alderink; Wendy K. Bernstein (Association of American Medical Colleges, 2019)
Introduction To assess communication and professionalism, as well as technical skills related to patient care, the American Board of Anesthesiology (ABA) has begun administering an Objective Structured Clinical Examination (OSCE) portion of the APPLIED Examination in addition to the Standard Oral Examination component. Methods We created video modules and a curriculum for anesthesiology resident OSCE preparation for the Interpretation of Monitors and Interpretation of Echocardiography components. The modules can be used individually by trainees or included as part of an OSCE workshop led by faculty educators with seven individual stations matching the content of the actual ABA examination. These modules are recommended for all levels of anesthesiology trainees so that they can gain exposure to the format and the fast pace of the examination. Results Sixty-six junior and senior anesthesiology residents, fellows, and junior faculty successfully participated in these modules. Seventy-three percent of the participants agreed that after completing these modules, they now had a good understanding of the Interpretation of Monitors and Interpretation of Echocardiography technical skills stations. More than 90% of participants reported that the modules were useful, and more than 70% reported that they now felt prepared for these stations of the OSCE. Discussion Developing technical skills stations for deliberate practice and preparation for the ABA OSCE is resource intensive. Finding time and faculty to facilitate OSCE preparation is also challenging. With the video modules and scripts included in this publication, residents can practice independently or as part of larger preparation course.